Junction City, Kansas in the 1930s - Mobley, Rebecca (Kansas State University. Dept. of History. Chapman Center for Rural Studies, 2010)
Rebecca Mobley describes African American life in Junction City, Geary County, in the 1930s. She examines the effect of the Great Depression on the black community, including descriptions of their residential areas, schools, livelihood, and churches. Her findings suggest discriminatory practices within an integrated school system but also, acceptance of the African Americans who settled very early in this area. The hard times of the 1930s created a shared experience for many Junction City residents.
Keywords: African American; Junction City; Geary County; Great Depression